2007
DOI: 10.1021/ja071185d
|View full text |Cite
|
Sign up to set email alerts
|

Structural Assembly of Multidomain Proteins and Protein Complexes Guided by the Overall Rotational Diffusion Tensor

Abstract: We present a simple and robust approach that uses the overall rotational diffusion tensor as a structural constraint for domain positioning in multidomain proteins and protein-protein complexes. This method offers the possibility to use NMR relaxation data for detailed structure characterization of such systems provided the structures of individual domains are available. The proposed approach extends the concept of using long-range information contained in the overall rotational diffusion tensor. In contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 48 publications
1
44
0
1
Order By: Relevance
“…S10. However, we found that one of these intermediate states (labeled I3) similar to the compact structure (PDB 2PE9) which was determined by NMR spectroscopy [34]. The compact X-ray structures might be resulted from the crystal packing forces, therefore are unstable in solution.…”
Section: Resultsmentioning
confidence: 65%
“…S10. However, we found that one of these intermediate states (labeled I3) similar to the compact structure (PDB 2PE9) which was determined by NMR spectroscopy [34]. The compact X-ray structures might be resulted from the crystal packing forces, therefore are unstable in solution.…”
Section: Resultsmentioning
confidence: 65%
“…This would allow us to account for side chain and backbone flexiblity at the inerface and integrate with all other available experimental data. A recent XPLOR-NIH implementation42 of the diffusion-tensor-guided docking method20 serves as an example. Third, PATIDOCK can be used as the main method for driving molecular docking in a situation where there is a lack of unambiguous intermolecular structural information, like NOEs.…”
Section: Discussionmentioning
confidence: 99%
“…In case of bimolecular systems, we have previously demonstrated that rigid-body alignment and docking of the molecules based on relaxation data alone can provide fairly accurate models for inter-molecular interactions (Ryabov and Fushman, 2007b; Berlin et al, 2011). In ROTIDF 3 we provide a built-in interface, described in the next section, that allows the user to seamlessly switch from simple derivation of the diffusion tensor to immediate quantification of the results (using ELMDOCK(Berlin et al, 2011)) in terms of intermolecular orientation and positioning, without requiring any additional input data or program parameters.…”
Section: Molecular Alignment Docking and Dynamicsmentioning
confidence: 99%
“…(Fushman et al, 1994; Bruschweiler et al, 1995; Mandel et al, 1995; Tjandra et al, 1995; Peng and Wagner, 1995; Tjandra et al, 1997; Fushman et al, 1997; Akke et al, 1997; Fushman and Cowburn, 1998b; Fushman et al, 1999b; Hall and Fushman, 2003; Fushman, 2012). Recently progress has been made on a number of fronts: (i) the improved ability to refine the structures of complexes and quantify molecular motion; (ii) the use of the diffusion tensor as a long-range orientational restraint for the structural characterization of multidomain systems (Fushman et al, 1999b; Ghose et al, 2001; Fushman and Cowburn, 2002; Fushman et al, 2004; Ryabov and Fushman, 2006, 2007a) and for analysis of dynamics of mostly the backbone of proteins (Hall and Fushman, 2003; Fushman et al, 2004; Hall and Fushman, 2006), and rarely for nucleic acid bases and ribose moieties (Akke et al, 1997; Legault et al, 1998; Hoogstraten et al, 2000; Dayie et al, 2002; Boisbouvier et al, 2003; Duchardt and Schwalbe, 2005; Eldho and Dayie, 2007) and (iii) introduction of rotational diffusion tensor as a translational restraint in rigid-body docking of multi-domain proteins and protein-protein complexes (Ryabov and Fushman, 2007b; Ryabov et al, 2010; Berlin et al, 2011). …”
Section: Introductionmentioning
confidence: 99%